Pengaruh Metode Problem Solving Terhadap Hasil Belajar Matematika Siswa Kelas V UPTD SD Negeri 124385 Jl Sawi - Belen Viorella Hutabarat; Janwar Tambunan; Minar T. Lumban Tobing (Jurnal Pendidikan Dasar Islam, 2024)
This research aims to determine the effect of the problem solving method on the mathematics learning outcomes of class V students at Uptd Sd Negeri 124385 Jl Sawi. This research is a type of experimental research in the form of Pre-Experimental Designs. The design used is one group pretest-posttest design. In this design there is a pretest, before treatment is given. In this way, the results of the treatment can be known more accurately, because they can be compared with the situation before the treatment. The sample data in this study were all class V students at SD Negeri 124385 Jl. Mustard. There were 11 female students and 9 male students, so the total sample size was 20 students. Based on the results of the research and discussion, it can be concluded that: Student learning outcomes are better. This is proven by the fact that before the researchers gave treatment, the students still had not completed the KKM, namely 20 students had not completed it. However, given the treatment of using problem solving methods in the learning process, student learning outcomes increased by 100%, namely that all 20 class V students successfully completed the KKM. The results of the hypothesis test show that ????h????????????????????= 23.372 and ????????????????????????=2.093. From these data it can be seen that ????hi????????????????>???????????????????????? then it can be concluded that ???????? is accepted, so there is an influence of the problem solving method on the mathematics learning outcomes of class V students at UPTD SD Negeri 124385 Jl. Mustard.